2022
DOI: 10.5339/jemtac.2022.13
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic diseases with mortality among hospitalized patients with COVID-19 treated with convalescent plasma: Evidence from a single center – Iraq

Abstract: Objective/Background: While there is no universal agreement on the benefits of convalescent plasma (CP) in the treatment of COVID-19 infection, very little is known about whether CP affects the association between chronic diseases and mortality. It is known that chronic diseases are associated with worse outcomes, but it is not clear whether the transfusion of CP impacts this association. This study aims to evaluate this impact considering that few studies have discussed the treatment of COVID-19 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Using leave-one-out analysis, three studies were identified as influential studies with an effect of 3.9% [ 41 ], 5.6% [ 47 ], and 3.6% [ 68 ] above the overall estimate of CAD prevalence. The pooled prevalence got adjusted to 13.2% [95% CI: 11.9–14.6] with an I 2 of 97.8% [95% CI: 97.5–98.0] after removing these 3 influential studies and studies with a high risk of bias [ 47 , 79 , 93 ]( Appendix C _ fig. C.2 and C.3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using leave-one-out analysis, three studies were identified as influential studies with an effect of 3.9% [ 41 ], 5.6% [ 47 ], and 3.6% [ 68 ] above the overall estimate of CAD prevalence. The pooled prevalence got adjusted to 13.2% [95% CI: 11.9–14.6] with an I 2 of 97.8% [95% CI: 97.5–98.0] after removing these 3 influential studies and studies with a high risk of bias [ 47 , 79 , 93 ]( Appendix C _ fig. C.2 and C.3 ).…”
Section: Resultsmentioning
confidence: 99%
“…C4 ). Further analysis was performed, removing the high risk of bias study [ 93 ]. The adjusted OR was 2.63 [95% CI: 2.29–3.02] with an I 2 of 45.0% [95% CI: 10.2–66.3] ( Appendix C _ fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-five to thirty percent of intensive care unit (ICU) patients contract a lower respiratory tract (LRT) infection caused by resistant bacteria, resulting in high rates of mortality (22-71%), morbidity, and death (8). There was a higher incidence of deaths attributable to COVID 19 among patients who had two or more chronic diseases compared to those who had no such diseases (9). Due to the effect of antibiotic use, the pattern of antibiotic resistance varies from one region to the next (10).…”
Section: Introductionmentioning
confidence: 99%